The Korean War and the post-war prisoners of war (POW) regime, 1945-1956 - Wylie, Neville; Crossland, James (SAGE Publications, 2015)
This paper examines the framework for the treatment of prisoners of war that emerged after 1945. It focuses on one of the key elements of the post-war prisoner of war (POW) regime, the role of neutral bodies – state authorities acting as ‘protecting powers’ or humanitarian agencies such as the International Committee of the Red Cross – in supervising the implementation of the 1949 POW convention. It examines the importance of neutral supervision for the POW regime, and shows how the events of the Korean War affected the willingness of states to comply with their obligations under the new convention.